Why do leaves change color - Maestro, Betsy; Krupinski, Loretta (New York, NY : HarperCollins, 1994)
Explains how leaves change their colors in autumn and then separate from the tree as the tree prepares for winter.
Keywords: Leaves -- Color -- Juvenile literature; Fall foliage -- Juvenile literature; Leaves; Fall foliage